Resahaping Global Trade throudh Sustainable E-commerce Ecosystems (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This paper analyzing how reshaping the future of global trade, explore the transition from traditional online retail models toward sustainable e-commerce ecosystems. By examining the integration of circular economy principles, green logistics, and ethical supply chain manajement, the study identifies the core drivers behind this transformation